PERANCANGAN SISTEM INFORMASI AKUNTANSI DENGAN MENGGUNAKAN DATABASE KARYAWAN UNTUK MENINGKATKAN KEAKURATAN DALAM MELAKUKAN PERHITUNGAN PENGGAJIAN PADA PT.DIS - BACHTIAR, ERWIN (Universitas Katolik Widya Mandala Surabaya, 2012)
The study was conducted on PT.DIS engaged in the production and distribution of ceramic. Payroll system by the company today is still less effective, which the company is still using the machine as a Check Clock which employee absences by doing it manually to the data card or Check Clock working hours and salary recapitulation data to Microsoft Excel. In addition, in Microsoft Excel has not been able to provide a database of employee and no limits on the use of an access password to the computer used to perform to the computer used to perform calculation employee salaries. By looking at these problems, it will be the evaluation procedures and payroll documents. Form these evaluation will be obtained a few weaknesses that the company will use the system. By knowing these knowing these weaknesses, it will be easy to looked for a solution, namely by the manual to computerized accompanied by making employee and is equipped with a database access restructions. With the new payroll system, expected to help PT.DIS in processing employee payroll. So it can provide the proper payroll information accurately and can also support the company in terms of decision-making.